POINT-BASED SUFFICIENT CONDITIONS FOR SHARP SOLUTIONS IN NONSMOOTH OPTIMIZATION - DUREA, Marius; FLOREA, Elena-Andreea; STRUGARIU, Radu (Journal of global optimization, 2025)
We present some sufficient optimality conditions for sharp and for isolated solutions of constrained scalar and set-valued nonsmooth optimization problems in terms of several types of subgradients and coderivatives. We make use of Shapiro properties for sets and the employment of different kinds of generalized differentiation objects allows to describe several degrees of sharpness. The main assertions generalize related results from literature.